A retrospective study investigating risk factors for sudden unexpected death in the young - Oghenechovwen, Ogheneochuko Mary (Department of Pathology, 2023)
Sudden unexpected death in the young (SUDY) is the unanticipated demise of individuals aged between 1 and 40 years. In South Africa, these deaths are referred for forensic investigation. The primary aim of this study was to retrospectively investigate the frequency of known risk factors in SUDY cases admitted to Salt River Mortuary in Cape Town and explore differences between males and females. There were 1 088 SUDY cases identified with 0.9% (10/1 088) missing files. Reviewed cases were n=1 078, 62.6% (675/1 078) males, and 37.4% (403/1 078) females; 83.5% (901/1 078) adults and 16.4% (177/1 078) children, accounting for 5.6% of total admissions between 1 January 2010 and 31 December 2015. Despite the predominance of males, significantly more females (61.8%) were obese (p < 0.05). At least one primary medical condition was present in 53.7% of cases, with the leading conditions being tuberculosis (11.9 % of adult males), epilepsy (11.7% of adult males; 10.3% of female children), HIV (10.7% of adult females) and asthma (11.1% of male children). In the subset of the study population where information was available, before death, 74% of individuals were reported to have experienced prodromal symptoms; 37.6% of males and 32.4% of females did not seek medical intervention following symptoms. Information regarding a family history of sudden death was known in 237/1078 cases. In 3.2% of these cases, a family history of sudden death was reported. Significantly more males than females reported the use of tobacco, alcohol, and other illicit drugs (p < 0.05). More females were unemployed (p < 0.05). Interventions based on lifestyle modification, social support, pharmacologic needs, and awareness should be targeted at individuals with the above profiles, especially those with a family history of sudden death, as they may be high-risk groups. Findings from this study contribute new and relevant local reference data for SUDY risk profiles of males and females admitted to Salt River Mortuary.